A Corpus-Based Study of High-Frequency Words in Madurese Textbooks for Elementary School - Zakiyah, Fitriyatuz; Susylowati, Eka (Linguistik : Jurnal Bahasa dan Sastra, 2025)
This research aims to analyze high-frequency words used in Madurese language textbooks for grade 4th, 5th, and 6th of elementary school students. The data in this study is a corpus created from two Madurese language textbooks for elementary schools used in grade 4th, 5th, and 6th in Bangkalan. The data was processed using concordance software, namely Lancsbox, to identify the vocabulary that are frequently used in those textbooks. Then, the data was analysed qualitatively to know the meaning and the word classes of the words. The results of this study show that the frequency of words that are most often used in textbooks in the three classes is the same, those are and “sè” which mean "yang". Additionally, in the Grade 4th textbook, out of 100 high-frequency words across the grades in the data, there are 7 parts of speech that are most frequently used. Those are nouns, particles, pronouns, verbs, adjectives, numerals, and adverbs. In the Grade 5th and 6th textbook, the part of speech that frequently used is nouns. It also used particles, pronouns, verbs, adjectives, adverbs, and numerals. the importance of text design that supports the transition from simple narrative learning in early grades to more information-dense and fact-based learning in later grades. It implies the importance of text design that supports the learning process. Moreover, these results can serve as a guide for educators and curriculum developers in creating more effective teaching materials, aligned with the development of language and student cognition.